Prevalence of crisis pregnancy center attendance among women in four U.S. states - Teresa J.K. Yang; Mikaela H. Smith; Megan L. Kavanaugh; JaNelle M. Ricks; Maria F. Gallo (PLoS ONE, 2025)
Objectives Crisis pregnancy centers (CPCs) typically hold missions of preventing abortion, opposing contraception, and promoting abstinence outside of marriage. They often lack transparency about their services, posing as medical facilities or even as abortion clinics. Given the lack of evidence on the extent to which people use crisis pregnancy centers, we sought to quantify the prevalence of ever attendance at a CPC among adult, reproductive-aged women from Survey of Women data from four states. Study design We analyzed cross-sectional data from population-representative surveys conducted among adult, reproductive-age women in 2018–2019 in Iowa (N = 2,425) and in 2019–2020 in Arizona (N = 2,132), New Jersey (N = 2,132), and Wisconsin (N = 2,095). Using survey weights, we calculated the prevalences of ever CPC attendance among those with a history of pregnancy or testing for pregnancy. We focused on this subset as this comprises the women who might have had cause to attend a CPC. We also used Poisson regression to test associations between demographic correlates and ever attendance by state. Results Prevalence of ever CPC attendance in adult, reproductive-age women with a history of pregnancy or testing for pregnancy was statistically significantly higher in Arizona (20.2%; 95% CI, 17.6%-23.1%) compared to Iowa (14.5%; 95% CI, 12.6%-16.7%), Wisconsin (14.3%; 95% CI, 12.1%-16.8%).), and New Jersey (11.6%; 95% CI, 9.6%-13.8%). Age, race/ethnicity, and socioeconomic status were not correlated with ever CPC attendance among women with a history of pregnancy or testing for pregnancy in Arizona, Iowa, and New Jersey. In Wisconsin, prevalence was lower among those in the lowest socioeconomic stratum. Conclusions Ever attendance at CPCs is not rare, ranging from 11.6%-20.2% in the four states evaluated. The present study serves as an important baseline given that the prevalence may change as pregnancy options become increasingly restricted.